Jean Prouvé : la Maison tropicale = [Jean Prouvé]. the tropical house - Prouvé, Jean. (Paris : Centre Pompidou, 2009)
Habitations démontables et maisons usinées dans le production des Ateliers Jean Prouvé=Portable and demountable dwellings, and manufactured homes produced by the Ateliers Jean Prouvé / Olivier Cinquiabre -- La Maison tropicale=The Tropical House / Oli
Includes bibliographical references.
French and English.
Keywords: Prouvé, Jean; Prouvé, Jean. Maison tropicale; Centre Georges Pompidou; Architecture, French -- History -- 20th century; Mimari, Fransız -- Tarih -- 20. yüzyıl